Energy performance of a new biomass harvester for recovery of orchard wood wastes as alternative to mulching. (August 2018) - Nati, Carla; Boschiero, Martina; Picchi, Gianni; Mastrolonardo, Giovanni; Kelderer, Markus; Zerbe, Stefan
Abstract: Woody crops such as orchards and olive groves require annual pruning operations, which leave abundant residues on the ground. These must be removed both for disease control and for facilitating the following tending activities. The resulting biomass can be managed as a waste or a by-product, in both cases incurring in a cost for farmers. A harvester prototype for collecting and comminuting apple pruning residues was tested and compared to a traditional mulcher. In particular, the study aimed at: 1) quantifying productivity and costs of the two systems, 2) evaluating the possible influence of apple variety, tree age and machine type on the productivity per hectare, and 3) estimating and comparing the energy balance of the two working options. The mulcher achieved a productivity of 0.41 ha SMH −1 against an average 0.27 ha SMH −1 of the harvester. Age of trees significantly influenced the productivity of both machines, with operative speed 42% higher in younger plantations. The cost of the operation added up to 137.5 € ha −1 and 275.2 € ha −1, respectively for the mulcher and the harvester. But the latter also produced 0.77 t dry matter ha −1 of biomass fuel suitable for in-farm use, whose value can cover most or the total of harvest costs. Accordingly, the energetic inputs amounted to 0.59 GJ ha −1 and 1.06 GJ ha −1 respectively for the mulcher and the harvester, while the recovered biomass provided an output of 6.30 GJ ha −1 for the latter system, resulting in a positive energy ratio (5:1). Graphical abstract: